Infection of Dice Snake, Natrix tessellata (Reptilia, Colubridae), with Eustrongylides excisus (Nematoda, Dioctophymatidae) in the Middle and Lower Dnipro River Basin - Yermolenko, S. V.; Gasso, V. A.; Hahut, A. M.; Spirina , V. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Dice snakes can be a paratenic host for a stage IV of Eustrongylides excisus, Jagerskiold, 1909 larva due to specific diet of the snakes. The infection rate of E. excisus in Natrix tessellate (Laurenti, 1768) was studied in the basin of the middle and the lower Dnipro River in 2013–2017. We searched for nematodes in snakes from four sites: Prydniprovska Thermal Power Station, Majorova Balka, Zaporizhzhia; National Nature Park Velykyi Luh. The snakes from all studied areas had high prevalence of infection (more than 90 %). The lowest level of intensity (2.50 ± 0.60) and abundance (2.27 ± 0.58) were in ecosystems near Prydniprovska ТPP. There was no significant difference between infection parameters in snakes from other groups. Capsules with larva localized in the gastrointestinal tract, liver, muscles, and lung. The most infected was the gastrointestinal tract, statistical analysis showed significant differences with other organs. The lowest infection was found in the lung. Environmental pollution of the Dnipro River waters with pesticides and other pollutants accompanied by a climate change may influence on the E. excisus life cycle that needs additional studies.